Chorea gravidarum: a rarity in West still haunts pregnant women in the East. (27th June 2013) - Pathania, Monika; Upadhyaya, Suneet; Lali, Bhagat Singh; Sharma, Archana
Abstract : A pregnant woman, in her early 20s, presents with chorea following an emotional outburst. While the family members feel it to be a spirit haunting her, we try to establish the medical diagnosis of the present condition. There is a history of rheumatic fever in the past and examination reveals choreioathetoid jerky movements of her upper limbs with jerky speech, spooning of her limbs and demonstration of milkmaid's grip. Laboratory investigations did not reveal anything interesting. We discuss the diagnosis and management of this patient.